2016
DOI: 10.1007/s00520-016-3256-5
|View full text |Cite
|
Sign up to set email alerts
|

Taxane acute pain syndrome (TAPS) in patients receiving taxane-based chemotherapy for breast cancer—a systematic review

Abstract: The incidence of TAPS varies between taxanes, regimens, and disease settings. In order to identify patients at the greatest risk of TAPS, and hence optimize its prevention and management, standardized methods of diagnosing and measuring TAPS are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 76 publications
0
21
0
2
Order By: Relevance
“…Prior exposure to taxane use has been considered a risk factor of musculoskeletal problems based on one small cross-sectional study [8], but this association was not observed in our retrospective cohort study using the population-based nation-wide data. Given that endocrine therapies are often initiated after taxane treatment [2], and taxane use may cause acute pain syndromes within two to three days after infusion and last for five to seven days [26], excluding women having a history of arthritis and carpal tunnel syndrome in the 12 months prior to endocrine therapy initiation in our study allowed us to evaluate the true effects of endocrine therapy on musculoskeletal problems. The affective disorders, including depressive disorder and anxiety, are known to impact the pain symptoms and the level of pain reported [27] and may be associated with medication non-adherence [28].…”
Section: Discussionmentioning
confidence: 99%
“…Prior exposure to taxane use has been considered a risk factor of musculoskeletal problems based on one small cross-sectional study [8], but this association was not observed in our retrospective cohort study using the population-based nation-wide data. Given that endocrine therapies are often initiated after taxane treatment [2], and taxane use may cause acute pain syndromes within two to three days after infusion and last for five to seven days [26], excluding women having a history of arthritis and carpal tunnel syndrome in the 12 months prior to endocrine therapy initiation in our study allowed us to evaluate the true effects of endocrine therapy on musculoskeletal problems. The affective disorders, including depressive disorder and anxiety, are known to impact the pain symptoms and the level of pain reported [27] and may be associated with medication non-adherence [28].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review to assess the incidence of the acute pain syndrome induced by taxanes in breast cancer patients, the authors concluded that pain was a clinically significant adverse event that interfered in the activities of daily living and reduced the participating patients' quality of life. (16) Untreated pain causes anxiety and depressive symptoms, also impairing the cognitive functions and entailing great losses in daily and social activities and sleep. The pain can act as a limiting factor for the accomplishment of activities of daily living and leisure, besides causing changes in the body image and reducing the frequency and pleasure of sexual activities; the pain can result in significant changes in the quality of life when compared to women without pain.…”
Section: Discussionmentioning
confidence: 99%
“…The neuropathy can continue for months and even years though. (16) This study's contributions related to the most detailed knowledge on Docetaxel-induced neuropathic pain, an important adverse reaction that affects women with breast cancer. This kind of studies supports the establishment of nursing interventions and can help with the management and reduction of neuropathic pain and its sequelae in the short, medium and long terms, contributing to improve the patients' quality of life through qualified nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, concomitant treatment with other neurotoxic chemotherapeutic agents, or pre-existing neuropathies, may additionally increase the risk of developing CIPN (Chaudhry et al, 2003). While symptoms usually develop within several weeks of treatment initiation, paclitaxel and docetaxel can also induce an acute painful neuropathy—peaking approximately 3 days after infusion—that is characterized by pain, numbness and tingling, and which can be a predictor for the development of chronic neuropathy (Loprinzi et al, 2007, 2011; Reeves et al, 2012; Tanabe et al, 2013; Fernandes et al, 2016). …”
Section: Cancer Chemotherapy: Drug Mechanism Of Action and Metabolitesmentioning
confidence: 99%